Pembagian Warisan Pada Masyarakat Muslim Suku Jawa Di Kecamatan Medan Sunggal - Ahmad Badawi (El-Ahli : Jurnal Hukum Keluarga Islam, 2020)
Shifting perspectives and applications Java society imigrants against inheritance systems is through the principle of gender equality, justice based role for a living, customs, and the other is an important issue that is interesting to conduct research of this thesis. Based on the description above, the problem in this study are as follows: How does the practice of inheritance in Java ethnic Muslim communities in the district Medan Sunggal? What is the basic argument variation inheritance in Java Adat Java ethnic Muslim communities in the district Medan Sunggal? How comparison implementation inheritance in Java ethnic Muslim communities in the district Medan Sunggal? This research was conducted in the District Medan Sunggal. Metode used in this study is a qualitative method by taking a sample of 50 respondents in distric Medan Sunggal. Data collected through; field observations, literature, interviews. After the observation is known that in the district Medan Sunggal has a number of Muslim communities Java ethnic group. While the results of the literature shows that the distribution of inheritance prevailing in Indonesia include three ways; Indigenous inheritance, in Islam, and Civil. The results of this study indicate that the legacy system prevailing in District Medan Sunggal by local custom that is ridla with ridla, one with the other. Keywords: Inheritance, Java Etnich